2013
DOI: 10.1007/s13277-013-0653-y
|View full text |Cite
|
Sign up to set email alerts
|

The curcumin analog DM-1 induces apoptotic cell death in melanoma

Abstract: SummaryThe main difficulty in the successful treatment of metastatic melanoma is that this type of cancer is known to be resistant to chemotherapy. Chemotherapy remains the treatment of choice and dacarbazine (DTIC) is the best standard treatment. The DM-1 compound is a curcumin analog that possesses several curcumin characteristics, such as antiproliferative, antitumor and antimetastatic properties. The objective of this study was to evaluate the signaling pathways involved in melanoma cell death after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Additionally, apoptosis was also confirmed by apoptotic bodies in human melanoma cell line. DM-1 antitumor therapy in vivo showed tumor burden decrease with DM-1 monotherapy or in combination with Dacarbazine, besides survival rate increase [13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, apoptosis was also confirmed by apoptotic bodies in human melanoma cell line. DM-1 antitumor therapy in vivo showed tumor burden decrease with DM-1 monotherapy or in combination with Dacarbazine, besides survival rate increase [13].…”
Section: Discussionmentioning
confidence: 95%
“…Activated pro-apoptotic proteins like Bid and Bax cause the release of the apoptogenic cytochrome-c from the mitochondrial membrane, leading to caspase cascade activation [44]. DM-1 also induces cytochrome-c release and electric mitochondrial membrane potential decrease in B16F10 melanoma cells after 6 h of treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…One strategy for circumventing this problem could be the creation of synthetic analogs. There were several reports on the new synthetic analogs or derivatives of curcumin to enhance the anti-proliferation activity (Faião-Flores et al, 2013;Kumaravel et al, 2012;Xiao et al, 2012), but these analogs generally led to cancer cell death via the apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that DM‐1 alone and in combination with DTIC induces apoptosis via the cleavage of caspase‐8, −3 and −9. These results indicated that DM‐1 shows therapeutic effects on melanoma via a preferential intrinsic apoptotic pathway by decreasing Bcl‐2/Bax ratio …”
Section: Curcumin Analogs As Powerful Tools In Melanoma Therapymentioning
confidence: 82%
“…Moreover, Faião‐Flores et al . revealed that curcumin analogue DM‐1, alone or in combination with dacarbazine (DTIC), shows anti‐tumor effects as it inhibited melanoma progression in a melanoma mouse model . In addition, no toxicological changes were observed in organs such as the spleen, kidneys, liver and lungs after the administration of DM‐1, either alone or in combination with DTIC.…”
Section: Curcumin Analogs As Powerful Tools In Melanoma Therapymentioning
confidence: 99%